THE EFFECT OF ADDING TOFU PULP FLOUR ON THE FIBER CONTENT OF SNACK BARS AS A HEALTHY SNACK ALTERNATIVE FOR TEENAGERS - Fatihah, Putri Fatma; Sofyaningsih, Mira (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Tofu residue flour is a by-product of the tofu production process that is rich in dietary fiber, but its use as a functional food ingredient is still limited in society. The purpose of this study was to utilize tofu production by-products to create a snack bar product as an alternative high-fiber snack. The parameters observed were chemical tests of tofu residue flour, the optimal snack bar formula, and dietary fiber content. The experimental design used was a completely randomized design with four treatment factors: F0 (100% wheat flour) as the control, F1 (60%), F2 (70%), and F3 (80%). Consumer acceptance testing was conducted on 50 untrained panelists to evaluate their preference for the snack bars based on indicators such as color, aroma, texture, taste, and overall. The results showed that the best snack bar was F1 (60%). Then then normality test and the Kruskal-Wallis follow-up test at a significance level of α = 0.05 indicated that the addition of tofu residue flour was associated with an increase in dietary fiber content in the produced snack bars, and there were significant differences in aroma and taste indicators. The proximate analysis and dietary fiber results for the best product per 100 g were as follows: total energy 435.85 kcal, ash content 2.035%, moisture content 15.49%, carbohydrates 47.125 g, total fat 21.19 g, protein 14.16 g, and dietary fiber 16.755 g.